2021
DOI: 10.3390/polym13040493
|View full text |Cite
|
Sign up to set email alerts
|

MXene Enabling the Long-Term Superior Thermo-Oxidative Resistance for Elastomers

Abstract: The ability of long-term thermo-oxidative resistance is very important for elastomers in application. However, many conventional antioxidants are difficult to realize the long-term thermo-oxidative resistance. To overcome this limitation, a design strategy is introduced by combing elastomers with MXene and natural rubber (NR) is chosen as a model material. MXene is efficient in absorbing oxygen and the generated free radicals in the NR matrix and can inhibit the diffusion of oxygen toward the interior. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Therefore, it can be reported that Ti 3 C 2 T x MXene can effectively protect NR nanocomposites from aging due to its free radical scavenging ability. [ 58,77 ] Based on our findings, the following antiaging mechanism of Ti 3 C 2 T x MXene is proposed ( Scheme ).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Therefore, it can be reported that Ti 3 C 2 T x MXene can effectively protect NR nanocomposites from aging due to its free radical scavenging ability. [ 58,77 ] Based on our findings, the following antiaging mechanism of Ti 3 C 2 T x MXene is proposed ( Scheme ).…”
Section: Resultsmentioning
confidence: 86%
“…A study has reported that NR with 7 wt% of MXene has shown about 60–70% retention of tensile strength and elongation at break upon aging at 100 °C for 3 days. [ 77 ] Further, the same author has reported around 10–30% retention of tensile strength and 45–65% retention of E@B upon aging of NR, which consists of different types of organic antioxidants. According to our results, the NRMX nanocomposites have shown about 80–90% and 60–78% retention of mechanical properties upon aging for 1 and 3 days at 100 °C, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To highlight the importance of phase transfer agent to properties of crosslinked elastomers, we compare tensile strength, tear strength, and elongation at break among this work and the elastomers with different accelerators in Figure 4 c,d. The data of elastomers with different accelerators are from the previous works, containing N-cyclohexyl-2-benzothiazolesulfenamide (CZ) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], diphenyl guanidine (D) [ 49 , 50 ], dibenzothiazyl disulfide (DM) [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ], 2-mercaptobenzothiazole (M) [ 2 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], N-tert-butylbenzothiazole-2-sulphenamide (NS) [ 30 , 66 , 67 , 68 , 69 , 70 , 71 ], and tetra methyl thiuram disulfide (TMTD) [ 30...…”
Section: Resultsmentioning
confidence: 99%